Biological Effects and Applications of Chitosan and Chito-Oligosaccharides - Guan, Guiping; Azad, Md. Abul Kalam; Lin, Yuanshan; Kim, Sung Woo; Tian, Yun; Liu, Gang; Wang, Hongbing (Frontiers in Physiology, 2019)
The numerous functional properties and biological effects of chitosan and chito-oligosaccharides (COS) have led to a significant level of interest, particularly with regard to their potential use in the agricultural, environmental, nutritional and pharmaceutical fields. This review covers recent studies on the biological functions of COS and the impacts of dietary chitosan and COS on metabolism. The majority of results suggest that the use of chitosan as a feed additive has favorable biological effects, such as antimicrobial, anti-oxidative, cholesterol reducing and immunomodulatory effects. The biological impacts reviewed herein may provide a new appreciation for the future use of COS.